Factors associated with professionalism in Chinese medical students: an exploratory cross-sectional study. (October 2016) - Fan, Angela P; Kosik, Russell O; Xu, Guo-Tong; Cai, Qiaoling; Lien, Selina; Huang, Lei; Zhao, Xudong; Zhang, Xiaojie; Wang, Yuhwa; Chen, Qi
Abstract: Background: Professionalism is a central part of medical practice, and medical organisations worldwide have mandated training on this topic for future medical doctors. In China, national guidelines were developed to make explicit expectations that were once implicit. Medical education reform over the past decade has emphasised topics such as medical humanities, life-long learning, and patient-centered learning in an effort to increase the professionalism of future physicians. Although the importance of teaching professionalism has been well recognised, few studies have evaluated its implementation at Chinese medical schools. Methods: We recruited medical students from three medical schools deemed to be representative of different regions in China (Tongji University School of Medicine, Shanghai (national); Nanjing Medical University, Jiangsu (provincial); Qiqihar Medical University, Heilongjiang (local)). We used the Jefferson Scale of Physician Empathy- Student Version (JSPES), Chinese version of the General Health Questionnaire, Center for Epidemiologic Studies Depression Scale (CES-D), Chronic Fatigue Syndrome assessment, and other personality and social status instruments to collect cross-sectional data. Statistical analyses were done using SPSS (version 20). Ethical approval was obtained by the Institutional Review Board of National Yang-Ming University. Findings: We recruited 914 participants to the study. The mean JSPES score of the total population was 105 (SD 20). National university (Tongji) medical students (109 [18]), female medical students (107 [20]), and medical students who had not yet reached their third year of medical school (110 [17]) had significantly higher levels of professionalism than those in their third year or above (99 [17]). Professionalism and empathy were significantly associated with chronic fatigue syndrome: those who had higher scores in professionalism scored less for chronic fatigue syndrome (Pearson Correlation, −0·203; p<0·0001. Professionalism was synergistically associated with personality, general health, and depression (p<0·0001). Statistically significant differences in personality (p<0·0001), general health (p=0·002), depression (p=0·001), and chronic fatigue syndrome (p<0·0001) were also found between students from the three universities. Interpretation: Chinese medical students in general have a positive disposition towards professionalism. Level of professionalism is highly associated with chronic fatigue syndrome, so medical educators should pay attention to curricular burden and provide support mechanisms aimed at reducing student stress. Funding: Republic of China Ministry of Science and Technology grant MOST104-2511-S-010-003 .